APPLICATION OF THE INQUIRY MODEL ON SCIENCE LEARNING OF VIBRATION AND WAVES - Sudaryani, Tati (Jurnal Kajian Pembelajaran dan Keilmuan, 2021)
AbstractThis study aims to obtain an increase in the learning activities of class VIII A students of SMP Negeri 5 Sungai Raya in the 2018/2019 academic year. Student learning activities in science learning material Vibration and Waves using the Inquiry Model in class VIII A SMP Negeri 5 Sungai Raya have increased every cycle, it can be seen from the level of student learning completeness per cycle, namely in cycle 1 based on the results of the pre test, the score is obtained the highest is 86.6 and the lowest value obtained is 46.6. The average pre-test value of the experimental class was 68.23. Meanwhile, based on the results of the post test, the highest score was 93.3 and the lowest score was 66.6. The average post-test score for the experimental class was 82.03. Then in cycle 2 based on the results of the pre test, the highest score was 100 and the lowest score was 53.3. The average value of the experimental class pre test is 77.21. Based on the results of the post test, the highest score was 100 and the lowest score was 86.6. The average post-test score for the experimental class was 97.92. There is a very significant change in the increase in student learning activities between the pre-test and post-test. Based on the Minimum Completeness Criteria (KKM) the percentage of students has increased.Â Â Keywords: Inquiry Model, Student Learning Activities